The hepatitis B virus reactivation after transarterial chemoembolization in Chinese hepatocellular carcinoma patients with low serum hepatitis B virus DNA level - Shao W; Zhang F; Cong N; Li J; Song J (Dove Medical Press, 2015)
Wenbo Shao, Fengjuan Zhang, Ning Cong, Jinpeng Li, Jinlong SongDepartment of Surgical Oncology (Interventional Therapy), Shandong Cancer Hospital and Institute, Shandong Academy of Medical Sciences, Jinan, People’s Republic of ChinaObjective: To investigate the reactivation of the hepatitis B virus (HBV) following transarterial chemoembolization (TACE) in Chinese hepatocellular carcinoma (HCC) patients with low serum HBV DNA level, and to analyze the factors related to HBV reactivation in HCC patients with low serum HBV DNA level.Methods: From November 2011 to January 2014, 109 patients newly diagnosed with HCC with an HBV DNA level less than 2,000 IU/mL were enrolled in the study. These patients underwent at least two TACE procedures and were followed-up for at least 3 months to assess the reactivation of HBV DNA. Ten variables were compared in patients with and without HBV reactivation to evaluate the factors related to HBV reactivation in HCC patients with low serum HBV DNA level.Results: Of 109 HCC patients with low level HBV DNA, nine patients were HBeAg-positive, the other 100 patients were HBeAg-negative. Twenty-three of 109 (21.1%) patients developed HBV reactivation after TACE. Of nine HBeAg-positive patients, 55.6% (5/9) developed HBV reactivation, while in 100 HBeAg-negative patients, the rate of HBV reactivation was 18% (18/100) (P=0.019). Of ten variables of patients with low level HBV DNA, the levels of AFP and HBeAg status were found to be significantly correlated with HBV reactivation. Nevertheless, on binary logistic regression analysis, only HBeAg-positive status was the independent predictor of HBV reactivation in HCC patients with low serum HBV DNA level (odds ratio, 7.41; P=0.013).Conclusion: HCC patients with low serum HBV DNA level still remain associated with risk of viral reactivation after TACE, and HBeAg-positive HCC patients have a higher risk than patients with HBeAg-negative status.Keywords: HBV DNA, viral reactivation, hepatocellular carcinoma, transarterial chemoembolization